2021
DOI: 10.1016/j.celrep.2021.109255
|View full text |Cite
|
Sign up to set email alerts
|

VEGFC/FLT4-induced cell-cycle arrest mediates sprouting and differentiation of venous and lymphatic endothelial cells

Abstract: Highlights d Endothelial cells sprout from the PCV in G1 phase of the cell cycle d VEGFC/FLT4/ERK induce p53-, p21-, and p27-mediated cellcycle arrest to enable sprouting d Forced G1 cell-cycle arrest results in ectopic sprouting of undifferentiated ECs

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 72 publications
1
21
1
Order By: Relevance
“…During zebrafish development, Vegfc acts in both an autocrine and paracrine manner to induce venous as well as lymphatic sprouting by inducing cell cycle arrest via Vegfr3. 32,66 Similarly, our data showing emilin2a expression by cECs and EPDCs during cardiac regeneration suggest that Vegfc acts in both an autocrine and paracrine manner to promote emilin2a expression. Importantly, we found that global overexpression of emilin2a stimulates coronary revascularization and reduces scarring after cardiac injury.…”
Section: Discussionmentioning
confidence: 55%
“…During zebrafish development, Vegfc acts in both an autocrine and paracrine manner to induce venous as well as lymphatic sprouting by inducing cell cycle arrest via Vegfr3. 32,66 Similarly, our data showing emilin2a expression by cECs and EPDCs during cardiac regeneration suggest that Vegfc acts in both an autocrine and paracrine manner to promote emilin2a expression. Importantly, we found that global overexpression of emilin2a stimulates coronary revascularization and reduces scarring after cardiac injury.…”
Section: Discussionmentioning
confidence: 55%
“…VEGFC has long been considered to be the main regulator of lymphangiogenesis ( 72 ). However, multiple studies indicate that it also plays an important role in regulating endothelial sprouting ( 73 75 ). These data raise the possibility that treatment with the anti-VEGFA antibody, bevacizumab, may not be sufficient to inhibit angiogenesis in pituitary tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from reduction of eNOS, DNA damage, mitochondrial dysfunction, oxidative stress, telomere dysfunction and other stressors induce several tumor suppressor genes including p53 and lead to cellular senescence, the permanent state of cell arrest. ( Jerafi-Vider et al, 2021 ; Sun and Feinberg, 2021 ). Cellular senescence is originally a physiological protective mechanism to prevent the development of tumor, however, when such senescent cells accumulate in number it leads to aging of cells ( López-Otín et al, 2013 ).…”
Section: P53 and Endothelial Dysfunctionmentioning
confidence: 99%